Physiological Characteristics of Sumatera’s Organic Chicken that was Raised in Cool and Hot Climate Regions - Elfawati elfawati; M. Hafil Abbas; Rusfidra rusfidra; Ahadiyah Yuniza (International Journal of Agricultural Sciences, 2019)
This study was aimed to analyze the physiological characteristics including respiratory rate, rectal temperature, and heterophil-lymphocyte (H:L) ratio of Sumatra’s organic chicken (SOC) that was raised in cool and hot climate regions. One-hundred-and-eighty-seven male and female SOC aged about 6 months were taken from cool and hot climate regions in Sumatera Island. Regions with cool climate were represented by highlands in West Sumatera including the subdistrict of Tilatang Kamang, Canduang, and East Padang Panjang. Regions with hot climate were represented by lowlands in Riau Province including the subdistrict of Bunga Raya, Lirik, and East Kampar. Samples of SOC were collected from farmers where the distance of sampling was about 500 m. Measurements were taken on respiratory rate, rectal temperature, and heterophil-lymphocyte ratio. Data was analyzed by t-test. The result showed that the respiratory rates of SOC in hot climate regions were higher than the ones in cool climate regions, the rectal temperatures of SOC in hot climate regions were lower than the ones in cool climate regions and there was no difference between the Heterophil:Lymphocyte ratio of SOC in hot climate and in cool climate regions.